REFLECTION AS A PHILOSOPHICAL PHENOMENON OF THE CONNECTION BETWEEN THE INDIVIDUAL AND SOCIETY (Scientific journal of the Fergana State University, 2026)
The article examines the phenomenon of reflection as a central philosophical concept that connects individual consciousness with social reality. Based on hermeneutic, phenomenological, comparative-historical, and structural-functional methods, reflection is presented as a universal mechanism of self-understanding and sociocultural interaction of the individual. It is noted that in the context of digitalization, reflection becomes the foundation of critical thinking, ethical responsibility, and the formation of personal identity.